The Role of Sabhara's Four Wheel Patrol in Preventing Motor Theft Crime Criminal Actions in The Jambi Polresta Legal Area - Rizki Kurniawan Tresnadi (Advances in Police Science Research Journal, 2021)
Motor theft crime crimes are rife in the jurisdiction of the Jambi Police, especially during the Covid-19 pandemic like this. In the past three years, the number of two-wheeled motor theft crime crimes has decreased in 2018 - 2020. In this case the role of four-wheeled patrols is very important because the activities carried out by the Sabhara Patrol Unit prevent the emergence of intentions and opportunities for motor theft crime perpetrators by conducting patrols. four wheels in the community as a preventive effort and this is the spearhead of the police's efforts in dealing with disturbances of security and public order. This study uses management theory from George R. Terry, the concept of the Motor theft crime Law, the concept of Patrol, the concept of roles, the concept of Prevention, Article 2 of Kabaharkam Regulation No. 1 of 2017 and Article 26 to analyze existing problems. This research uses a qualitative approach and field study methods (field research). The focus of research in this case is the activity of four-wheeled patrols in preventing criminal acts of Motor theft crime. Data collection techniques are interviews, observation and document study. Data analysis was performed by reduction, data presentation, and verification. The results of the study found that the implementation of the four-wheel patrol activities of the Sabhara Polresta Jambi unit was quite good in preventing the existing motor theft crime crime. However, there are still some problems. The Patrol concept in the regulations has not been properly implemented by the officers. Management in four-wheeled patrol activities is also lacking. From the results of the research conducted, the researchers provided suggestions, among others: To improve the quality of the Sabhara patrol members by providing education and training, optimizing the use of two-wheeled patrols, intensive supervision from the leadership, adding patrol members, and increasing cooperation with the community and other agencies